Racial/Ethnic Disparities in Self-Reported Pediatric Orthodontic Visits in the United States - Christopher Okunseri, BDS, MSc; Nicholas M. Pajewski, BS; Emily L. McGinley, MS, MPH (Blackwell Synergy, 2007)
Studies in orthodontics have focused primarily on clinical care and techniques.